How volunteering with extension 4-H youth development contributes to public value. Issue 4 (8th August 2021) - O'Neil, Kandi; Vettern, Rachelle; McGlaughlin, Patricia; Harrington, Rebecca; Maass, Sarah; Grant, Samantha; Good, Tillie
ABSTRACT: Volunteers add public value to the communities where they live and work leading to changes in community conditions. This study assessed volunteers' beliefs about perceived public value in the Extension 4-H Youth Development Program (YDP). Research results document Extension 4-H volunteers take active leadership roles, which leads to public value in communities. There is a direct application of skills gained as a result of their volunteer experience. Results provide evidence of how volunteers make a difference building social capital in four areas: increased civic involvement, better-connected communities, stronger communities, and improved community health. Contributions by 4-H volunteers not only make communities stronger; they benefit individuals beyond those involved in the 4-H program. Leaders are encouraged to further substantiate and communicate to stakeholders the public value of volunteer impact by assessing how volunteers contribute in public and private organizations throughout their communities.